2021
DOI: 10.1007/s00127-021-02142-5
|View full text |Cite
|
Sign up to set email alerts
|

The timing and duration of depressive symptoms from adolescence to young adulthood and young adults’ NEET status: the role of educational attainment

Abstract: Purpose Depressive symptoms are negatively associated with labour market outcomes but whether the timing and duration of depressive symptoms or educational attainment (EA) affect NEET (Neither in Employment, Education, nor Training) is unknown. Therefore, this study aims to examine the effects of timing and duration of depressive symptoms in adolescence and the moderating and mediating role of EA on NEET in young adulthood. Methods Data were used from 1512… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
(70 reference statements)
0
5
1
1
Order By: Relevance
“…Recent research shows that mental health problems in childhood and adolescence have a negative impact on young adult employment status (eg, having a paid job or not). [1][2][3][4][5][6][7][8] Previous studies mainly examined mental health problems in relation to young adults' employment status. Only a few examined the relationship between young adults with long duration mental health problems and employment status.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research shows that mental health problems in childhood and adolescence have a negative impact on young adult employment status (eg, having a paid job or not). [1][2][3][4][5][6][7][8] Previous studies mainly examined mental health problems in relation to young adults' employment status. Only a few examined the relationship between young adults with long duration mental health problems and employment status.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a study of Norwegian young people, self-reported conduct symptoms had a stronger effect on grade point average, years of schooling, and completion of upper-secondary education, than internalizing symptoms ( Evensen, 2019 ; Evensen et al, 2016 ). Moreover, Veldman et al (2022) showed that educational attainment did not mediate the relationship between adolescent depressive symptoms and NEET in early adulthood. The discrepancy between internalizing and externalizing symptoms may in part reflect the different social responses that internalizing and externalizing symptoms are met with in the school setting.…”
Section: Discussionmentioning
confidence: 92%
“…Due to both developmental sex differences and gendered norms and expectations for behaviour ( Martin & Hadwin, 2022 ), adolescent girls and young women tend to display higher levels of internalizing symptoms (characterized by inwardly focused symptoms like anxiety and depression), and boys and young men tend to display externalizing symptoms (characterized by externally focused behavioural symptoms such as aggression or oppositionality) ( Bongers et al, 2003 ; Rosenfield & Smith, 2010 ). While some studies have found stronger effects of distress or depression on NEET for boys than girls ( Henderson et al, 2017 ; Veldman et al, 2022 ), others show stronger effects for girls than boys ( Cornaglia et al, 2015 ). Still others have found evidence of gender-specific patterns, showing that internalizing symptoms are related to a higher likelihood of NEET for girls, whereas externalizing symptoms are more salient for boys ( Plenty et al, 2021 ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Así, esta perspectiva comúnmente ha relacionado esta problemática con variables como las individuales y familiares. Por ejemplo, se han considerado relevantes cuestiones como el ingreso familiar, la composición familiar, el género, las responsabilidades de cuidado familiar, la discapacidad, los problemas de salud al largo plazo, entre otros (Rasalingam et al, 2021;Schoon, 2014;Veldman et al, 2022).…”
Section: Niniunclassified